COMMUNICATIVE LITERACY AND MEDIA COMPETENCE IN THE HYPERCOMMUNICATIVE SOCIETY - Caldeiro-Pedreira, Mari Carmen (2015)
The communicative ecosystem develops and takes place in today’s technological society where hypercommunication is prioritized. Within this context, an enormous number of screens broadcast audiovisual contents that shape the recipients’ opinion and behavior. The different types of faceto- face and virtual interaction, as well as the media maelstrom, require training and literacy, not only communicative but also audiovisual, aimed at the attainment of a critical attitude through the development of the skills necessary for face-to-face and virtual communication. In this sense, this research intends to justify the interest and need for growth of media competence as a form of autonomous and critical expression. This topic attracts the interest of different national and international organizations and institutions, and is closely related to the media education that should be carried out by trainers and communication professionals.